The Effectiveness of Group Guidance Utilizing Symbolic Modeling and Behavior Contract to Enhance Self-Resilience Among Former Drug Addicts in Sleman Regency - Muhammad Faris Arief; Dwi Yuwono Puji Sugiharto; Ernest Ceti Septyanti (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
Resilience plays a key role in preventing relapse among former drug addicts. This study aims to evaluate the effectiveness of group guidance using symbolic modeling and behavior contract techniques to enhance self-resilience and compare their relative impacts. A quantitative approach with a pretest-posttest control group design was applied to 21 participants in Sleman Regency. Resilience was measured using the adapted Connor & Davidson Resilience Scale (CD-RISC). The Wilcoxon test analyzed within-group effectiveness, while the Kruskal-Wallis and Mann-Whitney tests compared effectiveness across groups. Findings show that symbolic modeling significantly improves resilience, whereas the behavior contract technique does not yield a significant effect. Moreover, there are notable differences in effectiveness among the symbolic modeling, behavior contract, and control groups. These results highlight the greater potential of symbolic modeling in enhancing resilience among former drug addicts in school-based rehabilitation programs